Patterns and predictors of mortality in the first 24 hours of admission among children aged 1–59 months admitted at a Regional Referral Hospital in South Western Uganda - Moses Ochora; Stella Kyoyagala; Lydia Kyasimire; Mercy Akambasisa; Margaret Twine; Muna Ahmed; Dan Lutasingwa; Dorah Nampijja; Elias Kumbakumba (PLoS ONE, 2025)
Most deaths among children under 5 years occur within the first 24 hours of hospital admission from preventable causes such as diarrhea, pneumonia, malaria, and HIV/AIDS. The predictors of these deaths are not yet well documented in our setting. This study aimed to describe the patterns and predictors of these mortalities among children aged 1–59 months at a regional hospital in South Western Uganda. We conducted a prospective cohort study among 208 children aged 1–59 months admitted to Mbarara Regional Referral Hospital. The mortality rate within the first 24 hours was 7.7% (95% CI 4–12) and the median time to death was 7.3(2.62–8.75) hours. Most deaths occurred in infants, with severe pneumonia, severe acute malnutrition, and malaria as leading causes. Factors predicting mortality included admission during the night (AHR: 3.7, 95% CI 1.02–13.53, p-value 0.047) and abnormal neutrophil count(AHR: 3.5, 95% CI 1.10–11.31, p-value 0.034). The study highlights the importance of timely interventions, particularly for infants, and suggests extra monitoring for those admitted at night or with abnormal neutrophil counts.